Typical suburban scene. Trinidad, B.W.I. - (:unkn) unknown (Published for Cunard S.S. Co. by Picture-Point Publications, 2010)
This photograph illustrates a typical suburban scene in Trinidad, British West Indies. Three men traverse the wide concrete street. Two of them are on foot and the third one is riding on a bicycle. Various types of single story houses line the street. A vintage automobile approaches. Coconut palms are everywhere and a mountain can be seen in the distance.
Colour: Coloured; Style: Landscape; Other: Unbordered, Undivided
Keywords: Trinidad and Tobago; Postcards; Trees--Coconut palm; Bananas; Automobiles